Three basic open access software tools for academic analysis of photocatalytic particles - Mendoza-Acosta, Alexander; Torres-Romero, Suleyka; Orozco, Martín; Cota, Manuel; Basurto, Ricarda L.; Galaviz, Luis L. (Frontiers in Chemical Engineering, 2023)
There is currently a great interest in photocatalytic degradation technologies of pollutants in industrial effluents, this is due to the need to reduce the environmental pollution generated by the textile industry derived from the high demands of clothing in the fast fashion modality, which in addition to presenting severe environmental problems also generates social problems. Since the catalysts of this type of processes are usually nanoparticles of metal oxides such as Zinc and Titanium, it is necessary to promote research in the synthesis and evaluation of photocatalysts, so this article describes three basic tools of free access for the academic analysis of nanoparticles, which cover various phases from experimental design to representation, logically going through the study of kinetics and particle size analysis. After a pre-selection of easily accessible software it was found that RStudio, J-Image and Vesta are very useful programs in the analysis of nanoparticles in the respective areas of statistical processing, image analysis and three-dimensional representation.